Ways and means for managing up : 50 strategies for helping you and your boss succeed - Smullen, F. William (McGraw Hill-Ascent Audio, 2014)
Today's typical workplace may be less formal and more inclusive than those of the past, but one thing hasn't changed: The boss is the boss. A veteran of the U.S. Army, William Smullen spent 50 years leading--and being led by--some of the toughest people in the business. Over his career, he served at every level from platoon to division--and at the highest levels in the Pentagon, as well. In business terms, that's the equivalent of running a very small business to sitting in a corporate C-Suite. Smullen's final public-service assignment was chief of staff to Secretary of State Colin L. Powell. As chief of staff, one of his main responsibilities was to ensure Secretary Powell kept his positive image and was successful in everything he did. Now, he shares the lessons he learned working in some of the world's most demanding organizations. In Ways and Means for Managing Up, he tells you everything you need to know to effectively "manage your manager" in ways that help both you and your boss succeed and rise within your company. In 50 short yet informative chapters, Smullen shares his hard-won insight, such as: View your relationship with your boss as a partnership Think of your boss as a brand Never allow your boss to be surprised Help your boss manage risk or crisis Be a strategic asset your boss counts on Whether you're good friends with your manager or have trouble coexisting in the same office, your success depends on his or her success. This has always been true, and it will always be true. You serve yourself well when you serve your boss well. Take your career to new heights by learning and applying the Ways and Means for Managing Up. It can serve as a survival guide, a road map, or a blueprint for people at every level in an organization.